A comparison of plyometric training techniques for improving vertical jump ability and energy production - Gehri, D. J.; Ricard, M. D.; Kleiner, D. M.; Kirkendall, D. T. (The Journal of Strength and Conditioning Research, 1998)
Gehri et al (1) assigned 28 subjects to either a control group, a depth jump group, or a countermovement jump group. The depth jump group performed a depth jump training program two days a week for 12 weeks. The countermovement group performed a training program involving countermovement jumps two days a week for 12 weeks. Testing was performed before and after the 12 week program; subjects were tested for performance in the squat jump, countermovement jump, and depth jump. The results show that a depth jump and countermovement jump program appear equally effective in improving vertical jump height and positive energy production.